Effects of Sex and Notch Signaling on the Osteocyte Cell Pool. Issue 2 (7th June 2016) - Canalis, Ernesto; Schilling, Lauren; Zanotti, Stefano
Abstract : Osteocytes play a fundamental role in mechanotransduction and skeletal remodeling. Sex is a determinant of skeletal structure, and female C57BL/6J mice have increased osteoblast number in cancellous bone when compared to male mice. Activation of Notch in the skeleton causes profound cell‐context dependent changes in skeletal physiology. To determine the impact of sex and of Notch signaling on the osteocyte cell pool, we analyzed cancellous and cortical bone of 1–6‐month‐old C57BL/6J or 129SvJ/C57BL/6J mice and determined the osteocyte number/area. There was an age‐dependent decline in osteocyte number in cancellous bone of male but not female mice, so that 6‐month‐old female mice had a greater number of osteocytes than male littermates. Although differences between male and female mice were modest, female mice had ∼10–15% greater number of osteocytes/area. RNA sequence analysis of osteocyte‐rich preparations did not reveal differences between sexes in the expression of genes known to influence bone homeostasis. Neither the activation of Notch1 nor the concomitant inactivation of Notch1 and Notch2 in Osterix ( Sp7 ) or Dentin matrix protein 1 ( Dmp1 ) expressing cells had a pronounced and consistent effect on cancellous or cortical bone osteocyte number in either sex. Moreover, inactivation of Notch1 and Notch2 in Dmp1 expressing cells did not influence the bone loss in a muscle immobilization model of skeletal unloading. In conclusion, cancellous bone osteocytes decline with age in male mice, cortical osteocytes are influenced by sex in younger mice, but osteocyte cell density is not affected substantially by Notch signaling. J. Cell. Physiol. 232: 363–370, 2017. © 2016 Wiley Periodicals, Inc. Abstract : In the present paper the impact of sex and Notch signaling on the osteocyte cell pool was determined by bone histomorphometry. There was an age‐dependent decline in osteocyte number in male but not female mice. Female mice had 10–15% greater number of osteocytes than male mice. Notch activation and inactivation had limited influence on osteocyte number, and Notch inactivation did not modify the effects of unloading on the skeleton.